Pengaruh Dana Pihak ketiga Non Performing Loan dan Suku Bunga Kredit terhadap Profitabilitas pada PT. BPR Suryajaya Ubud - Ni Kadek Egi; Ade Maharini Adiandari (Institut Ilmu Sosial dan Manajemen Stiami, 2020)
This study aims to determine the effect simultaneously or partially on profitability at PT. BPR Suryajaya Ubud for the period 2013-2016. The sample used was 48 DPK, NPL, Loan Interest Rates, and ROA data. Data were analyzed using the classic assumption test, multiple linear regression test, determination analysis, simultaneous significance test (F-test), and partial significance test (t-test). The results in this study indicate that Third Party Funds have partially negative and significant effect on ROA. Non Performing Loans partially have a negative and significant effect on ROA. Credit interest rates partially have a positive and significant effect on ROA. DPK, NPL, and Credit Interest rates simultaneously have a significant effect on ROA at PT. BPR Suryajaya Ubud in 2013-2016.